Presenting a Causal Model of Mentalization with the Mediating Role of Mothers’ Emotional Regulation and Emotional Instability in Adolescents’ Emotional-Behavioral Disorders - Zabihi, Marzieh; Ghasemi Motlagh, Mehdi (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to develop and examine a causal model of mothers’ mentalization with the mediating roles of mothers’ emotion regulation and emotional instability in adolescents’ emotional-behavioral disorders.Methods and Materials: The present study employed a correlational design using path analysis within the framework of fundamental research. The statistical population consisted of all mothers and their adolescent children aged 16 to 18 years in Mashhad during the 2024–2025 academic year. Using multistage cluster sampling, 420 mothers and their 420 adolescent children were selected. The research instruments included the Emotional and Behavioral Problems Questionnaire developed by Achenbach and Rescorla (2003), the Mentalization Questionnaire developed by Dimitrijevic et al. (2017), the Mentalized Affectivity Scale (MAS) developed by Greenberg et al. (2017), and the Difficulties in Emotion Regulation Scale (DERS) developed by Gratz and Roemer (2004). Data were analyzed using Structural Equation Modeling (SEM) through IBM SPSS Statistics and LISREL software packages.Findings: The findings indicated that the proposed model demonstrated satisfactory fit indices (RMSEA = .02, CFI = .99, IFI = .99, GFI = .99, χ²/df = 1.13). Mothers’ mentalization had a significant direct negative effect on adolescents’ internalizing problems (β = -0.41, p = .001) and externalizing problems (β = -0.12, p = .023). In addition, mothers’ mentalization showed a significant positive effect on mothers’ emotion regulation (β = 0.45, p = .001) and a significant negative effect on mothers’ emotional instability (β = -0.12, p = .008). The indirect effects analysis revealed that mothers’ emotion regulation and emotional instability significantly mediated the relationship between maternal mentalization and adolescents’ emotional-behavioral disorders.Conclusion: The findings suggest that mothers’ mentalization plays a substantial role in reducing adolescents’ emotional-behavioral disorders both directly and indirectly through improving emotion regulation and reducing emotional instability.